Ethnic Segregation in Arizona Charter Schools - Cobb, Casey D.; Glass, Gene V (Education Policy Analysis Archives, 1999)
Among the criticisms of charter schools is their potential to further stratify schools along ethnic and class lines. This study addressed whether Arizona charter schools are more ethnically segregated than traditional public schools. In 1996-97, Arizona had nearly one in four of all charter schools in the United States. The analysis involved a series of comparisons between the ethnic compositions of adjacent charter and public schools in Arizona's most populated region and its rural towns. This methodology differed from the approach of many evaluations of charter schools and ethnic stratification in that it incorporated the use of geographic maps to compare schools' ethnic make-ups. The ethnic compositions of 55 urban and 57 rural charter schools were inspected relative to their traditional public school neighbors.